Analisis kebijakan pembiayaan pendidikan dalam perspektif pendidikan agama Islam di Indonesia - Zamsiswaya Zamsiswaya; Mulyadi Wilis (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2026)
Islamic Religious Education (PAI) in Indonesia faces critical budget management challenges, despite the 20% education allocation in the amended 1945 Constitution. This study aims to analyze the effectiveness of PAI education activity budgets and formulate sharia-based management strategies for optimization. A descriptive qualitative method was employed, utilizing secondary document analysis (APBN reports from the Ministry of Finance 2021-2026, Kemenag regulations) and quantitative efficiency ratios (madrasah BOS data). Key findings reveal PAI budget proportion at 18-20% of total education spending (Rp 712 trillion in 2025), yet low efficiency (70% BOS absorption due to weak administration and regional disparities). SWOT analysis highlights opportunities for integrating productive waqf and maqasid shariah to strengthen Islamic character building. Strategic implications include recommendations for SIMKAT-Kemenag digitalization and performance-based allocation, supporting the Merdeka Curriculum for PAI. This research contributes to holistic and sustainable strategic management in Islamic education in Indonesia.